Penerapan Artificial Intelligence untuk Kontrol Suhu dan Kelembapan pada Kandang Broiler berbasis Internet of Things - Nalendra, Adimas Ketut; Waspada, Heri Priya (Generation Journal, 2021)
Abstract – Broiler chickens or broiler chickens are one of the popular sources of nutrition in Indonesia. The production of broilers reaches 3.15 billion heads, with the most production center on Java’s island. The Covid-19 disaster that hit Indonesia caused broilers’ production to decrease due to the government’s social restrictions. To maximize production and reduce production efficiency, artificial Intelligent application innovations are carried out for temperature, humidity, and gas control in broiler chicken coops. Artificial Intelligent methods of developing machines can think like humans to help control and make decisions. This artificial Intelligent model uses a fuzzy logic Pulse Width Modulator (PWM)model. The device used for control utilizes Internet of Things technology with a microcontroller as its primary device and sensor as an environmental data reader. The microcontroller used is ESP32 which has been embedded with Wifi to facilitate the transmission of data to the server. To read the sensors’ environmental conditions used by temperature sensors, humidity uses DHT11 and ammonia gas using MQ2. Environment data is sent to the server, which is useful for the user monitoring the cage environment’s condition remotely and, if needed, can be controlled by using the application interface. In this research, the process of system development using waterfall method, namely needs analysis, design, implementation and testing. The system’s application results were tested using two models, namely, trying the sensor reading value compared to the weight on the hygrometer and observation of the reaction of chickens in the cage. The test results obtained the difference in value between the sensor and hygrometer can be tolerated and the chicken reaction following the system’s cooling status.